"Call me by my name": Names, address, and the subjectivization of Korean women. (July 2022) - Milak, Eldin
Abstract: Personal names in South Korea are subject to avoidance and restrictions in use grounded in the asymmetric relations of power and age that constitute the sociolinguistic ideologies of the country. At the same time, as lexical items which are inherently and conventionally referential, names have the unique reformational power to change normative social practice. The affordances provided by the dual status of names allow speakers to (re)negotiate relational parameters and reposition themselves as subjects in the wider spatiotemporal setting. The focus on female speakers reveals internal tensions between names and restricted forms of address in familial settings, where the selection and usage of names is interpreted as movement of Korean women towards subject positions on both micro-interactional and macro-social scales. Highlights: Being called by name is an unusual occurrence in South Korea. In Korean families, limited access to names results in the indexical erasure of women. Preference for name-calling implies a shift towards greater subjectivity and agency. Changes in address reflect a preference for more egalitarian interactive fields.